Care of Older Persons in Eastern Africa: A Scoping Review of Ethical Issues - Kirubel Manyazewal Mussie; Jenny Setchell; Bernice Simone Elger; Bernice Simone Elger; Mirgissa Kaba; Solomon Tessema Memirie; Solomon Tessema Memirie; Tenzin Wangmo (Frontiers Media S.A., 2022)
IntroductionThe aging population is rapidly increasing globally, with 80% of the older population living in low- and middle-income countries. In Eastern African countries, there exists an incongruence between readiness-economically, structurally, politically, and culturally-to create a conducive environment for healthy aging, which implies public health as well as ethical concerns. The aim of this scoping review was to explore existing evidence addressing the various ethical issues in connection with elder care in the region of Eastern Africa.MethodsWe searched six databases (Africa-Wide Information, AgeLine, CINHAL, MEDLINE, APA PsycInfo, and SocINDEX) to identify peer-reviewed journal articles that could meet some eligibility criteria such as being a peer-reviewed journal article written in English, having been published in any year until July 2020, and focusing on ethical issues in the care of older people aged 60 years and older from Eastern Africa. We also searched for additional evidence in the references of included papers and web-based platforms. We included 24 journal articles and analyzed them using the inductive content analysis approach.ResultsThe included articles represent seven (38.9%) of the 18 countries in the Eastern African region. The articles covered six ethical concerns: lack of government attention to older persons (n = 14, 58.3%), inaccessibility of health care services (n = 13, 54.2%), loneliness and isolation (n = 11, 45.8%), gender inequalities in old age (n = 9, 37.5%), mistreatment and victimization (n = 8, 33.3%), and medical errors (n = 2, 8.3%).ConclusionThis scoping review summarized ethical issues arising in relation to providing care for older persons in the Eastern African context. In light of the rapid increase in the number of older persons in this region, it is critical for governments and responsible bodies to implement and accelerate efforts promptly to generate more evidence to inform programs and policies that improve the health and wellbeing of older persons. Further research is needed to inform global health efforts that aim at improving the lives of older persons, particularly in low- and middle-income countries.Clinical Trial Registrationhttps://osf.io/sb8gw, identifier: 10.17605/OSF.IO/SB8GW.